Clinical outcomes of stereotactic body radiotherapy for elderly patients with hepatocellular carcinoma. Issue 2 (24th June 2017) - Teraoka, Yuji; Kimura, Tomoki; Aikata, Hiroshi; Daijo, Kana; Osawa, Mitsutaka; Honda, Fumi; Nakamura, Yuki; Morio, Kei; Morio, Reona; Hatooka, Masahiro; Kobayashi, Tomoki; Nakahara, Takashi; et al.
Abstract : Aim: To evaluate the safety and efficacy of stereotactic body radiotherapy (SBRT) for the treatment of hepatocellular carcinoma (HCC) in elderly patients. Methods: From 2008 to 2015, 117 patients with HCC (≤3 nodules, ≤30 mm in diameter, Child–Pugh score ≤7, and no vascular or extracellular metastasis) were treated with SBRT at our hospital. We evaluated overall survival (OS), disease‐free survival (DFS), local control, and adverse events. Patients were stratified according to age 75 years and older (elderly group, n = 54) and age younger than 75 years (young group, n = 63). Results: The median OS in the elderly group was not significantly different from that in the young group (52 months vs. not reached, P = 0.27). The 1‐, 2‐, and 3‐year OS rates were 96.2%, 77.6%, and 63.9%, respectively, in the elderly group, and 96.8%, 84.8%, and 67.7%, respectively, in the young group. The median DFS in the elderly group was significantlyshorter than that in the young group (13 vs. 25 months, respectively; P = 0.03). The 1‐, 2‐, and 3‐year DFS rates were 50.6%, 30.4%, and 26.6%, respectively, in the elderly group and 66.5%, 50.7%, and 45.3%, respectively, in the young group. The 3‐year local tumor control rate in the elderly group was 98.1%, and that in the young group was 98.4% ( P = 0.83). There was no difference between groups in the incidence of any adverse events. Conclusions: Stereotactic body radiotherapy can be effective and safe for the treatment of HCC in elderly patients.